Basic English an Effort to Improve the Ability of Kip Scholarship Students at Mandalika University of Education - Kamarudin, Kamarudin; Imran, Fathurrahman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
English language teaching has not been evenly distributed across all regions in Indonesia. The tendency is that students who go to school in big cities have better English teaching than remote areas. On the other hand, KIP Scholarship students come from many regions, some of which come from outside big cities. KIP Scholarship students are students with good academic backgrounds but have weak economic abilities. For KIP Scholarship students, they do not have the capital to get access to additional language learning facilities even if they need it. In the end, their competitiveness will be low. Therefore, the Basic English skills of KIP College Scholarship students need to be improved in order to be more competitive. In this study, Basic English was given to KIP Kuliah Scholarship students of Mandalika University of Education who were most in need of capacity building. A total of 12 meetings, in addition to the pretest and posttest, were organized. As a result, the Basic English skills of KIP College Scholarship students improved. However, it still takes perseverance from students to want to learn better so that their skills improve significantly. It can be concluded that the Basic English Implementation program for KIP College Scholarship students helps improve the ability of human resources in the field of English.